ANALISIS HARGA, PENDAPATAN, DAN PERMINTAAN BAHAN POKOK DI MEDAN: SUATU KAJIAN LITERATUR - Deni Adriani; Anisa Fitria Sinaga; Diana Puspitasari; Fransiska Adelia Br Sinulingga (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
Price is one of the most important marketing factors and prices also influence consumer purchasing decisions. However, the importance of this factor is meaningless if companies do not understand how price influences consumer purchasing decisions and its role in creating competitive advantage. The discussion in this study aims to analyze the effect of prices and consumer income on the demand for basic commodities in the city of Medan. This study uses a literature review by collecting the theoretical basis of the relationship between demand and price in determining consumer income from the existing literature and analyzing the literature. The findings of the study show that there is a positive relationship between the price and demand variables on the income variable, so that in order to increase a seller, the price and demand must be increased. However, in the relationship between price and demand variables there is a positive relationship where the greater the price, the smaller the demand.Keywords: Price, Income and Demand for Basic Materials